(untitled) (Journal of Science and Technology, 2024)
During the COVID-19 pandemic, institutions were forced to shut down and adopt online tools for teaching and learning. In the context of design faculties, the quest to equip students with practical skills demanded an e-learning experience that was robust and similar to in-person lectures. Though studies have been done on different aspects of e-learning during the COVID-19 pandemic, the online learning experiences of design students have not been explored extensively. This study, therefore, aimed at exploring design students’ experiences with e-learning during the COVID-19 pandemic using Activity theory as a lens. The study used a focus group discussion with twenty-five students who were grouped into six. The data gathered were thematically analysed. The findings show that the students were mentally prepared for online learning due to their exposure before the pandemic and thus students could use the online tools very well with little assistance from lecturers and their colleagues. Thus, students’ preparation, innovative thinking for solutions, lecturers’ guidance, the use of social media tools along mainstream e-learning tools and colleagues’ support were successful factors for the communication design students’ positive practical experience of e-learning during the COVID-19 pandemic. Notwithstanding the positive experiences, some challenges were encountered by the students, which included high data cost, high data consumption by some of the e-learning tools, screen fatigue as well as poor connectivity disrupted the flow of some of the virtual lessons.